Chromosome-Level Genome Assembly of the Hemiparasitic Taxillus chinensis (DC.) Danser. (28th April 2022) - Fu, Jine; Wan, Lingyun; Song, Lisha; He, Lili; Jiang, Ni; Long, Hairong; Huo, Juan; Ji, Xiaowen; Hu, Fengyun; Wei, Shugen; Pan, Limei
Abstract: The hemiparasitic Taxillus chinensis (DC.) Danser is a root-parasitizing medicinal plant with photosynthetic ability, which is lost in other parasitic plants. However, the cultivation and medical application of the species are limited by the recalcitrant seeds of the species, and even though the molecular mechanisms underlying this recalcitrance have been investigated using transcriptomic and proteomic methods, genome resources for T. chinensis have yet to be reported. Accordingly, the aim of the present study was to use nanopore, short-read, and high-throughput chromosome conformation capture sequencing to construct a chromosome-level assembly of the T. chinensis genome. The final genome assembly was 521.90 Mb in length, and 496.43 Mb (95.12%) could be grouped into nine chromosomes with contig and scaffold N50 values of 3.80 and 56.90 Mb, respectively. In addition, a total of 33, 894 protein-coding genes were predicted, and gene family clustering identified 11 photosystem-related gene families, thereby indicating photosynthetic ability, which is a characteristic of hemiparasitic plants. This chromosome-level genome assembly of T. chinensis provides a valuable genomic resource for elucidating the genetic basis underlying the recalcitrant characteristics of T. chinensis seeds and the evolution of photosynthesis loss in parasitic plants.